Kreasi Olahan Nugget Dari Jantung Pisang Sebagai Alternatif Cemilan Sehat - Titin Supriyatin; Fitri Damayanti; Avini Nurazhimah Arfa (Jurnal Pengabdian Masyarakat Biologi dan Sains, 2022)
Shifts in lifestyle and food consumption patterns of the community have an influence on the nutritional status of the community. Along with the development of science and technology, people are faced with an unhealthy lifestyle, people tend to prefer and like the types of practical and fast food, soft drinks that are widely circulated in the market or contemporary drinks that are trending in society, lack of exercise, unbalanced diet, and much more. Based on the results of observations made, it shows that in the Jl. Budi Mulia RT 04 RW 07, Pademangan, North Jakarta that teenagers in this area consume high levels of fast food. One way for optimal health is to regulate the food consumed by paying attention to good nutritional intake. then our community service team will provide training on making "Nugget Processed Creations from Banana Hearts as an Alternative for Healthy Snacks" and obtained data that: 1. As many as 17 people or 85% answered that they had never made nuggets from banana hearts before, 2. as many as 19 people or 95% answered that they would make nuggets from banana hearts after receiving training, 3. as many as 15 people or 75% answered that they would make nuggets from banana hearts after receiving training as a business opportunity.